The Effect of Product Quality and Brand Image on Marjan Syrup Purchase Decisions in the South Jakarta Area - Shaffa Najma Auliya; Djoko Hananto (Eduvest - Journal of Universal Studies, 2026)
This study investigates the influence of product quality and brand image on purchasing decisions for Marjan syrup in the South Jakarta area. The research was conducted against the backdrop of a consistent decline in syrup consumption and sales performance throughout early 2024, indicating the need for companies to optimize key marketing variables that shape consumer behavior. Using a quantitative approach, the study employed a survey method with 150 respondents selected through purposive sampling, representing consumers who had purchased Marjan syrup in the designated region. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS 27. The findings reveal that product quality has a positive and significant effect on purchasing decisions, demonstrating that consumers prioritize functional performance, durability, and overall value when choosing syrup products. Similarly, brand image also shows a significant positive influence, indicating that a strong, trustworthy, and emotionally resonant brand perception can strengthen consumer preference and drive purchase intention. Together, both variables contributed a substantial 91.3% of the variance in purchasing decisions, confirming their strategic importance in shaping market behavior. These results highlight the necessity for companies to maintain superior product quality while consistently strengthening brand positioning to remain competitive amid shifting consumer preferences. The study underscores the relevance of integrating marketing strategy with consumer behavior insights to sustain growth and optimize sales performance in the beverage industry.